Investigating the Effects of Several Parameters on the Growth of Chlorella vulgaris Using Taguchi’s Experimental Approach - Barghbani, R.; Rezaei, K.; Javanshir, A. (International Journal of Biotechnology for Wellness Industries, 2012)
Algae are part of photosynthetic organisms that play an important role in the aquatics nutrition. Like plants, algae need water, light and CO2 to grow. Using Taguchi’s experimental approach (5 factors in four levels with 16 runs), effects of several parameters (NaCl, sodium bicarbonate and iron concentrations as well as light and temperature) on the growth of Chlorella vulgaris was studied. Increasing the concentrations of NaCl and sodium bicarbonate resulted in corresponding decreases in the growth of C. vulgaris. Media with 30.0 g/l NaCl did not indicate any algal growth. Also, with 9.0 g/l sodium bicarbonate, biomass production was decreased. Chlorella vulgaris showed different growing behaviors at the various concentrations of iron (Fe+2) and at the different temperatures of this study. Maximum biomass production (approximately 3.56 g dry matter) was obtained at the 0.0 g/l sodium bicarbonate, 10.0 g/l NaCl, 18.0 µmol/l iron and at 30±2 °C. Yellow and blue lights increased the algal growth. Analysis of variance showed that salinity (i.e., the NaCl concentration) had the highest impact on the biomass production.